SUBSTANTIATION OF LAND MANAGEMENT DESIGN SOLUTIONS IN THE DEVELOPMENT OF A COMPREHENSIVE PLAN FOR SPATIAL DEVELOPMENT OF TERRITORIES - Dudych , Г. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The study aims to justify land-use design solutions for developing a comprehensive plan for spatial development in various territories. This plan will address economic, ecological, and social aspects to ensure sustainable development and the rational use of land resources. The research focuses on land management solutions at the level of territorial communities, highlighting the complex development of these areas as a significant scientific issue. Addressing this challenge is crucial for fostering the development of rural regions. Modern land management is a multifaceted activity that involves scientifically justifying land distribution according to its intended purpose, while considering state, public, and private interests. It also encompasses organizing rational land use and protection, regulating land and ecological relations, forming sustainable land use, and establishing a rational system of land ownership. The study outlines the information necessary for effective land management measures concerning prospective land use, which are based on developed project solutions. It also notes the conditions under which land plots may be forcibly alienated for social necessity reasons. The research demonstrates the importance of analyzing the current state of territories and proposing effective land management solutions when creating a comprehensive plan for spatial development. The resulting scheme of land management measures for prospective land use includes objects that may be subject to alienation. This approach involves several stages: analyzing the current state of the territory, determining zones for residential, commercial, industrial, agricultural, and recreational activities, and considering environmental and historical-cultural aspects to facilitate effective land resource use and promote sustainable development in the territories.